Parametric analysis of space nuclear power plants in thermodynamic design variables - A.G. Yuferov; V.A. Linnik; M.A. Nikolaev (Nuclear Energy and Technology, 2015)
The purpose of the study is to analyze the influence of efficiency factor and medium-entropy temperatures on the specific mass of a space power plant and the specific area of the radiator cooler with regard for heat losses and mass coefficients of subsystems. Functions of the specific performance sensitivity to variations of design variables are used as the parametric analysis tool. It has been shown that sensitivity functions represent criteria relations that define the optimality and similarity range for space nuclear power plants (SNPP) of different types. To specify the permissible intervals for the variation of design variables, a form has been proposed for recording the specific characteristics with explicit interrelationships between target functions and design variables. The obtained results demonstrate a single-extremum dependence of the considered specific characteristics on generalized design variables. This makes it reasonable to define the optimization problem based on the said criteria of the SNPP technical level.